2017
DOI: 10.18632/oncotarget.22469
|View full text |Cite
|
Sign up to set email alerts
|

F-box proteins in epigenetic regulation of cancer

Abstract: Epigenetic abnormalities are now realized as important as genetic alterations in contributing to the initiation and progression of cancer. Recent advancements in the cancer epigenetics field have identified extensive alterations of the epigenetic network in human cancers, including histone modifications and DNA methylation. F-box proteins, the substrate receptors of SCF (SKP1-Cullin1-F-box protein) E3 ubiquitin ligases, can directly and indirectly affect the balance of epigenetic regulation. In this brief revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Interestingly, the KDM2B PHD domain also exhibits an E3 ubiquitin ligase activity [59]. KDM2A and KDM2B are the only members of the JmjC family that contain a C-terminal F-box domain [48,[92][93][94]. As opposed to the KDM2A F-box domain, whose function is still elusive, the KDM2B F-box domain has been shown to mediate protein-protein interactions.…”
Section: Kdm2a and Kdm2b: Cpg Island Binding Lysine Demethylasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the KDM2B PHD domain also exhibits an E3 ubiquitin ligase activity [59]. KDM2A and KDM2B are the only members of the JmjC family that contain a C-terminal F-box domain [48,[92][93][94]. As opposed to the KDM2A F-box domain, whose function is still elusive, the KDM2B F-box domain has been shown to mediate protein-protein interactions.…”
Section: Kdm2a and Kdm2b: Cpg Island Binding Lysine Demethylasesmentioning
confidence: 99%
“…Although the JmjC domain of JARID2, a member of the JmjC domain-containing protein family, is not active due to amino acid substitutions in comparison to catalytically active JARID1, its loss-of-function phenotype is embryonically lethal and JARID2 is essential for early development [127]. On the other hand, FBXL19, a member of the F-box family proteins resembles KDM2A/B-SF since it contains the CXXC, PHD, F-box and LRR domains, but completely lacks the JmjC demethylase domain [48,93,94,128]. Despite lacking demethylation activity, FBXL19 plays an important role as a substrate-recognition component of the SCF (SKP1-CUL1-F-box protein)-type E3 ubiquitin ligase complex [93,94], and it has recently been shown to be essential for mouse development [128].…”
Section: Kdm2a/b-sf: Isoforms Of Lysine Demethylases With No Demethylation Activitymentioning
confidence: 99%
“…45 However, the F-box domain is not only limited to cyclin F, but identified in a number of proteins in budding yeast and vertebrate species. 48,49 Studies have shown that either working in concert with the SCF complex or alone, F-box proteins function in several cellular scenarios including cell cycle progression, synapse formation, plant hormone responses, and the circadian clock. 47 The F-box proteins have the ability to control the degradation of several crucial proteins associated with drug resistance, and dysregulation of these proteins contribute to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…47 The F-box proteins have the ability to control the degradation of several crucial proteins associated with drug resistance, and dysregulation of these proteins contribute to cancer development. 48,49 Studies have shown that either working in concert with the SCF complex or alone, F-box proteins function in several cellular scenarios including cell cycle progression, synapse formation, plant hormone responses, and the circadian clock. 50 Cyclin F is one of the several classes of cyclins identified continuously since 1983, 51 and they fall into classes based on their structural similarity, timing of expression and functional points within the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Clec-39 and Clec-49 protein-deficient nematodes became sensitive to Serratia marcescens infection [69]. F-box proteins (FBPs) contribute to cell proliferation, cycle, apoptosis, migration, invasion, metastasis [70,71], and antiretroviral function [72,73].…”
Section: Transcriptomic Analysis Of C Elegansmentioning
confidence: 99%